Interleukin-18 and Procalcitonin Factors as Predictors of Early-Onset Neonatal Sepsis - Devi Gusmaiyanto; Efrida Efrida; Hardisman Hardisman; Mayetti Mayetti (GLOBAL HEALTH SCIENCE GROUP, 2025)
Neonatal sepsis is a leading cause of morbidity and mortality worldwide, and one of the most common causes of neonatal death (15%). Early-onset neonatal sepsis (ESNAD) has a higher case-fatality rate than late-onset neonatal sepsis (SNAL). The gold standard for neonatal sepsis diagnosis is bacterial detection through blood culture, but this test has limitations such as being time-consuming and not being available in all health facilities. This study aims to determine the relationship between perinatal risk factors, hematological parameters in infants, procalcitonin, IL-18 with the incidence of SNAD. The population of this study were all babies who had risk factors for SNAD according to the PP Idai UKK Neonatology Clinical Practice Guidelines. The research sample was infants from an accessible population who met the inclusion and exclusion criteria. To fulfill statistical rules and fulfill the requirements for data analysis, in this study a minimum of 30 of each will be taken. The use of umbilical cord blood is a promising diagnostic tool in the diagnosis of SNAD. The IT and CRP ratios are elevated in umbilical cord blood from birth and are good indicators for detecting SNAD in infants at risk of infection. Umbilical blood procalcitonin is elevated in infants born >32 weeks with proven sepsis and low in infants with risk factors but without proven sepsis. Therefore, it is concluded that umbilical blood procalcitonin is a promising biomarker for detecting SNAD. IL-18 serves as a risk variable for neonatal sepsis. IL-18 has good discriminatory ability in the diagnosis of neonatal sepsis.